Current issue of clonal oil palm (Elaeis guineensis) for yield improvement: a review / Nornazihah Abdul Hadi - Abdul Hadi, Nornazihah (Faculty of Plantation and Agrotechnology, 2017)
By the year of 2020, it is expected the demand of palm oil will be increased with the number of people in the world population rising rapidly year by year. The demand for palm oil sources is very high so the yield should be increased to cater the demand. The biotechnology approaches through plant tissue culture technology could solve the shortage of oil palm sources the problem of shortage of palm oil sources. The plant tissue culture method can produce an elite clone. The multiple number of callus production with noble characteristic can directly help the industry of agriculture sector to meet the demand. Approaches have been chosen that method should be suitable to conduct the research as it is the main component that needs to be emphasized to ensure the production of high quality seedlings. Specialization explants chosen should be appropriate, because the palm trees have characteristics that are similar to other plants. The choosen of explants in tissue culture production of palm oil is a big impact because not all media that is produced is suitable for use in this field. Planned media care is very important because it affects the growth and activation of callus. Examples of care components of media that must be emphasized is that as the pH, temperature, plant growth hormone and photoperiod number, which is required. These elements have been identified to be a good stimulant for the growth of callus but it has certain values to support that growth. The present invention provides a very large impact on the agribusiness industry because the total number of oil palm saplings can be doubled with the higher and have values that can be commercialized and bring benefits to the country.